2015
DOI: 10.1002/adfm.201502166
|View full text |Cite
|
Sign up to set email alerts
|

BN–Graphene Composites Generated by Covalent Cross‐Linking with Organic Linkers

Abstract: Composites of boron nitride (BN) and carboxylated graphene are prepared for the fi rst time using covalent cross-linking employing the carbodiimide reaction. The BN 1-x G x ( x ≈ 0.25, 0.5, and 0.75) obtained are characterized using a variety of spectroscopic techniques and thermogravimetric analysis. The composites show composition-dependent electrical resistivity, the resistivity decreasing with increase in graphene content. The composites exhibit microporosity and the x ≈ 0.75 composite especially exhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…Figure 7A shows that after 10,000 times of rapid charge and discharge tests, BN:G(1:2) electrode has only 4% loss, exhibiting its excellent electrochemical stability. This is because h-BN has extremely high chemical and thermal stability, providing synergies with high electrochemical stability when it exists in conductive graphene systems (Kumar et al, 2015). Figure 7B shows the AC impedance diagram of BN/G samples with different mass ratios.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7A shows that after 10,000 times of rapid charge and discharge tests, BN:G(1:2) electrode has only 4% loss, exhibiting its excellent electrochemical stability. This is because h-BN has extremely high chemical and thermal stability, providing synergies with high electrochemical stability when it exists in conductive graphene systems (Kumar et al, 2015). Figure 7B shows the AC impedance diagram of BN/G samples with different mass ratios.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental results revealed that the lube base oil with 0.04 mg mL −1 h‐BNNPs‐ODTES produced a 16% reduction in friction coefficient and a 40% decrease in wear scar diameter. In addition, the preparation of surface‐functionalized h‐BN by covalent cross‐linking has attracted widespread interest among researchers . Kumar et al prepared a series of graphene‐BN composites by covalent cross‐linking using organic linkers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the preparation of surface‐functionalized h‐BN by covalent cross‐linking has attracted widespread interest among researchers . Kumar et al prepared a series of graphene‐BN composites by covalent cross‐linking using organic linkers. Inspired by this, the 3‐aminopropyltriethoxysilane (APTS) and 4‐carboxyphenylboronic acid (CPBA)‐grafted h‐BNNSs are designed and synthesized, which can be used as potential lubricant additives.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to the lack of sufficient binding sites on the surface of pristine h‐BN, where the metal nanoparticles are bounded only by weak non‐covalent interactions. On the other hand, despite several studies on the morphology, properties and preparation of organic modified h‐BN, no metal has been immobilized onto organic‐functionalized boron nitride as a heterogeneous catalyst. Herein, we report the first production of Pd catalyst based on β‐CD modified h‐BN, as a separable and recyclable catalyst for Suzuki and Heck coupling reactions.…”
Section: Introductionmentioning
confidence: 99%